School libraries in national minority schools - Radolović, Debora (Qualitative and Quantitative Methods in Libraries, 2020)
The world of education is changing, and changes affect all its components. Libraries operating in the education system see their role through a support of the education process they are ties to. By transforming their services, modern libraries meet the growing educational requirements while simultaneously taking on an increasingly significant place in the field of education. In the past, libraries have focused on their funds and their size as a measure of their own quality and importance. Today, given the needs and requirements of the contemporary environment, educational orientation is necessary for all libraries, especially libraries operating in the education system . This paper deals with the importance and impact of school libraries providing support to the education of pupils of national minorities' schools. The paper deals specifically with the school libraries of the Italian national minority operating within the educational system of the Republic of Croatia. The aim of this paper is to show the activity of school libraries in Italian national minority schools and their importance for the creation of a sound intercultural cooperation and life in the majority community.